The Phenomenon Of Begging Culture and Review According To Islamic Ulama’s - Ash-Shiddieqy, Syiehd Achmed Farhan (FKIP UNSULTRA, 2025)
Poverty is a social problem that is still a concern for the government today. Poverty has positive and negative impacts on human life. The negative impact is that poverty causes a high number of beggars. The purpose of writing this journal is to review research on the phenomenon of the current begging culture in Indonesia and collect the opinions of scholars regarding the law of begging so that the importance of conducting this research. The results of this study, namely: 1). That the phenomenon of begging culture has mushroomed in today's times and raises social problems for society, such as: vagrancy, sawer gifts via streaming platforms, silver humans, buskers and street clowns. 2). The ruling on begging, according to the scholars, is basically haram However, there are circumstances in which it is permissible to beg if it is an emergency.